Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd003712.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial laser revascularization versus medical therapy for refractory angina

Abstract: There is insufficient evidence to conclude that the clinical benefits of TMLR outweigh the potential risks. The procedure is associated with a significant early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
2
15
0
1
Order By: Relevance
“…Indeed, total and cardiac mortality, which are in the range of 6-10% and 4-6% per year, respectively, are similar in SCS patients to those [44]) and European (b, [49]) prospective registries, respectively. reported in patients with RAP randomized in the placebo arms of studies assessing the effect of myocardial laser revascularization (51). Similar results also have been shown for the occurrence of nonfatal acute myocardial infarction, which in SCS patients has been reported in the range of 3-5% per year.…”
Section: Scs and The Issue Of Ischemic Pain Inhibitionsupporting
confidence: 79%
“…Indeed, total and cardiac mortality, which are in the range of 6-10% and 4-6% per year, respectively, are similar in SCS patients to those [44]) and European (b, [49]) prospective registries, respectively. reported in patients with RAP randomized in the placebo arms of studies assessing the effect of myocardial laser revascularization (51). Similar results also have been shown for the occurrence of nonfatal acute myocardial infarction, which in SCS patients has been reported in the range of 3-5% per year.…”
Section: Scs and The Issue Of Ischemic Pain Inhibitionsupporting
confidence: 79%
“…Over the past two decades, results from prospective and retrospective studies on TMR have been reported. 15 31 A few meta-analyses have also been reported, along with an FDA review on short-term and long-term outcomes with the use of TMR. 29 , 31 33 This review covers two different FDA-approved devices for TMR, evidence-based practice, and future directions aimed at utilizing a combined TMR and stem cell therapy approach.…”
Section: Introductionmentioning
confidence: 99%
“…Specific limitations preclude wide acceptance of these methods. TMLR is associated with high early mortality (6.8% 30-day mortality rate) [7] . Molecular therapies via the coronary artery and cardiac surgery have both failed to support revascularization of the myocardium [8] .…”
Section: Introductionmentioning
confidence: 99%